Perancangan Sistem Informasi Penjualan Bahan Kimia Dan Perlengkapan Laundry Pada Toko Kimia Dan Parfume Ciledug Berbasis Web Mengunakan Metode Rapid Application Development - Nupia Sarpina; Dimas Abisono Punkastyo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Online information media with various forms and functions that have spread to all areas of life today is one of the impacts of the use of the internet which has become a global network and communication throughout the world. The internet can also be used as a medium of communication, especially in the business field in a company or agency, one of which is Ciledug Chemical and Perfume Stores. Ciledug Chemical and Parfume Store is a store that sells various types of chemicals and laundry equipment, the order transaction process in this store is via telephone or customers come directly to the store and choose the products they need. Besides, the process of managing data is still done manually, namely in the form of recording in books and the possibility of data being lost and damaged. Therefore, this research was conducted to design a sales website at the Chemical and Parfume Store in order to promote products that are sold widely and make it easier for consumers to make purchases without having to come directly to the store. This online application system can provide information for shop owners, employees, and customers which can be accessed anytime and anywhere. In making this application the author uses a Web Server with the PHP programming language, then for the database using Mysql. This information system was created using the Rapid Application Development method and a text editor used by Visual Studio Code.